Pregnancy and the eye - Kubicka-Trząska, Agnieszka; Karska-Basta, Izabella; Kobylarz, Joanna; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
During pregnancy periodical hormonal, metabolic, hematological, vascular and immunological changes can be observed, that can influence the function of the eye. Some of them can be observed in an eye due to pregnancy itself and would resolved spontaneously postpartum. Pregnancy can also induce or aggravate the preexisting conditions such as diabetic retinopathy or uveal melanoma. The autoimmune intraocular inflammation is modified by pregnancy manifesting by regression of the ocular symptoms. Pregnancy can have also beneficial effects on glaucoma because intraocular pressure has been reported to decrease during pregnancy. The presence of any ocular symptoms in a pregnant woman requires urgent ophthalmic examination and further management.